Drought and migration: Evidence from the Kyrgyz Republic - Kamalbek Karymshakov; Dastan Aseinov; Dina Azhgaliyeva (Asian Development Bank Institute (ADBI), 2024)
This study empirically examines the effect of the drought of 2021 on migration in the Kyrgyz Republic. A panel dataset was created using nationally representative household survey data for the period 2019-2022 with approximately 5,000 households in each year and integrated with the satellite data on precipitation at the community level to measure the drought. Empirical estimations based on the difference-in-differences method with fixed effects show that international migration of household members living in drought-affected locations increased during the post-shock year. Both urban and rural households demonstrated a positive migration trend. This finding suggests that policy aimed at creating resilience to the drought shock should be comprehensive and take into consideration its economy-wide effects.
Keywords: Q54; F22; O15; 330; migration; climate change; drought; Central Asia; Kyrgyz Republic